2012
DOI: 10.1021/bi301425r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of AlgL, an Alginate Lyase from Pseudomonas aeruginosa

Abstract: Alginate lyase (AlgL) catalyzes the cleavage of the polysaccharide alginate through a β-elimination reaction. In Pseudomonas aeruginosa algL is part of the alginate biosynthetic operon, and although it is required for alginate biosynthesis, it is not clear why. Steady-state kinetic studies were performed to characterize its substrate specificity, and revealed that AlgL operates preferentially on non-acetylated alginate or its precursor mannuronan. Mature alginate is secreted as a partially acetylated polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
(59 reference statements)
3
32
0
Order By: Relevance
“…4). These observations are consistent with findings of Farrell et al 49. which showed that AlgL displayed a surprising lack of stereospecificity to various alginates, further arguing that AlgL functioned exclusively to degrade misguided alginate in the periplasm without being directly involved in its polymerization, modification, and translocation/secretion process.…”
Section: Discussionsupporting
confidence: 92%
“…4). These observations are consistent with findings of Farrell et al 49. which showed that AlgL displayed a surprising lack of stereospecificity to various alginates, further arguing that AlgL functioned exclusively to degrade misguided alginate in the periplasm without being directly involved in its polymerization, modification, and translocation/secretion process.…”
Section: Discussionsupporting
confidence: 92%
“…For poly-ManA the specific activity (68.5 Ϯ 2.9 units/mg at pH 9) was also significant (Fig. 5B), being within an order of magnitude to the reported values for poly-ManA-specific lyases (31,46,47). Likewise, whereas the specific activity for HA (42.3 Ϯ 1.3 units/mg at pH 5) was the lowest for the three major substrates (Fig.…”
Section: Heterologous Expression and One-step Purification Ofsupporting
confidence: 71%
“…Determination of the kinetic parameters for degradation of low viscosity alginate by Alg17c was carried out using the thiobarbituric acid assay method ( (23) and Atu3025 from A. tumefaciens (9). Kinetic parameters for wild-type and site-specific active site variants of Alg17c are reported in Table 2 and discussed in the relevant sections below.…”
Section: Resultsmentioning
confidence: 99%